Effects of Meteorological Factors and Atmospheric Pollution on Hand, Foot, and Mouth Disease in Urumqi Region - Ren, Fang-rong; Abodurezhake, Yakup; Cui, Zhe; Zhang, Miao; Wang, Yu-yu; Zhang, Xue-rong; Lu, Yao-qin (Frontiers in Public Health, 2022)
Abstract Background: Hand, foot, and mouth disease (HFMD) is a febrile rash infection caused by enteroviruses, spreading mainly via the respiratory tract and close contact. In the past two decades, HFMD has been prevalent mainly in Asia, including China and South Korea, causing a huge disease burden and putting the lives and health of children at risk. Therefore, a further study of the factors influencing HFMD incidences has far-reaching implications. In existing studies, the environmental factors affecting such incidences are mainly divided into two categories: meteorological and air. Among these studies, the former are the majority of studies on HFMD. Some scholars have studied both factors at the same, but the number is not large. and the findings are quite different. Methods: We collect monthly cases of HFMD in children, meteorological factors and atmospheric pollution in Urumqi from 2014-2020. Trend plots are used to understand the approximate trends between meteorological factors, atmospheric pollution and the number of HFMD cases. The association between meteorological factors, atmospheric pollution and the incidence of HFMD in the Urumqi region of northwest China is then investigated using multiple regression models. Results: A total of 16,168 cases in children are included in this study. According to trend plots, the incidence of HFMD shows a clear seasonal pattern, with O3 (ug/m3) and temperature (°C) showing approximately the same trend as the number of HFMD cases, while AQI, PM2.5 (ug/m3), PM10 (ug/m3) and NO2 (ug/m3) all show approximately opposite trends to the number of HFMD cases. Based on multiple regression results, O3 (P=0.001) and average station pressure (P=0.037) are significantly and negatively associated with HFMD incidences, while SO2 (P=0.102), average dew point temperature (P=0.072), hail (P=0.077), and thunder (P=0.14) have weak significant relationships with them.